Influence of precision livestock farming on the environmental performance of intensive dairy goat farms. (1st June 2022) - Pardo, Guillermo; del Prado, Agustín; Fernández-Álvarez, Javier; Yáñez-Ruiz, David R.; Belanche, Alejandro
Abstract: The implementation of Precision Livestock Farming (PLF) concepts has been pointed out as an indirect strategy that could potentially help mitigating the environmental impacts of livestock production systems. To date, few studies have focused on analyzing specifically the relationship among PLF adoption and environmental performance, so sustainability benefits have not yet been quantified for many technologies. Moreover, studies evaluating the environmental impact of dairy production have traditionally focused on cattle, and when exploring sheep or goats, they have often involved extensive, low-productive systems, providing an incomplete picture of the sector. In this study we apply life cycle assessment (LCA) to analyze the environmental impact associated to intensive dairy goat production, and to explore the influence of adopting a smart-farming PLF platform on the environmental performance of a group of dairy goat farms in Spain. The PLF-platform relies on systematic on-farm monitoring of individual animal data, coupled with big data processing and interpretation, which supports farmers to take adequate -and timely-farm management decisions. In order to capture its influence, two different periods were analyzed in five selected farms: a baseline year just before innovation was implemented (2014) and four years after (2018), when most of the effect of improved management was reflected. Results after the PLF-platform implementation showed significant reductions (−11%) in greenhouse gas emissions and similar trends in other impact categories (9–16% reductions). The PLF platform provided a precise monitoring of the productivity, genetic merit and physiological state of each animal, allowing adequate criteria for a number of decision-making processes, such as selecting animals for breeding, replacement or culling. This optimization led to an increase in the genetic selection progress, ultimately reflected on milk productivity. Moreover, a reduction of unproductive periods such as first partum age or dry period length was often achieved. As a result of this general improvement, the efficiency of resource usage in relation to milk (and meat) production was increased, with positive effect on the environmental performance. Production of 1 kg of fat and protein corrected milk (FPCM) resulted in 1.53–1.71 kg CO2 eq. Results in other impacts categories were also in a similar range than previously reported values for highly productive dairy systems, including dairy cattle, which stresses the important role that small ruminant farming can play on environmentally sustainable livestock production, particularly in the Mediterranean context. Highlights: Environmental impact of goat milk is reduced through precision livestock farming. Improvement in animal breeding, genetic progress and unproductive periods. Harmonized LCA methods better show environmental footprint of small ruminants. Carbon footprint of goat milk is in a similar range than cow milk.